Pengaruh Persepsi Siswa Tentang Lingkungan Sekolah, Motivasi Belajar dan Aktivitas Belajar Terhadap Hasil Belajar Siklus Akuntansi Siswa SMK Bidang Bisnis Manajemen di Kota Solok. - Betri Herlina; Yulhendri Yulhendri (Program Magister Pendidikan Ekonomi (S2), 2015)
This research had some purposes that were to analize : ( 1) the influence of students perception about of school environmentand learning motivation toward the students’ learning activities (2) the influence of students peception about of school environment, learning motivation and students’ learning activities toward the students learning result. This research was quantitative with using survey. The population of this research was all of the students of accounting skill program at grade X, XI and XII of SMK bussines management in solok city in the academic year 2014/2015. There were416 students. The technique used in this research was proportionate random sampling which was 204 students.The data analysis was path analysis. Table f and t was as hypothesis. Data analyzed shown are :(1) students peception about of school environmentand learning motivationsignificance influenced toward the students’ learning activities (2) students perception about of school environment,learning motivation and students’ learning activities significance influenced toward the students’ learning activities. Directly significance is higher from indirectly significance. Based on the results it is suggested to the school to pay more attention to the school environment either physical or non-physical . For the teacher is perhaps to give reward to achievement students to increase the learning motivation of students.